2006
DOI: 10.1111/j.1469-7610.2005.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability and criterion validity of the Chinese version of CBCL, TRF, and YSR

Abstract: Clinicians should be cautious about score/case attenuation at retest while using CBCL, TRF, and YSR to chart patients' progress. They should also recognize their different strengths in screening various disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
172
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(186 citation statements)
references
References 7 publications
9
172
1
Order By: Relevance
“…The CBCL and TRF scales are appropriate for ages 4 through 18 years and have satisfactory internal consistency (αs > .80) and test -retest reliability (rs > .80) in large-sample epidemiological studies with Chinese youth aged 6 -11 years (Leung et al, 2006;Liu et al, 1999Liu et al, , 2000. Leung et al (2006) 4.7% (parents' reports) or 5.0% (teachers' reports) of the children in the present sample had clinically significant externalizing problems. The BPI externalizing scale includes 11 items, all of which are represented in the CBCL and TRF externalizing scales.…”
Section: Ce (W2)-children Completed the Seven-item Coping Efficacy Scmentioning
confidence: 96%
See 3 more Smart Citations
“…The CBCL and TRF scales are appropriate for ages 4 through 18 years and have satisfactory internal consistency (αs > .80) and test -retest reliability (rs > .80) in large-sample epidemiological studies with Chinese youth aged 6 -11 years (Leung et al, 2006;Liu et al, 1999Liu et al, , 2000. Leung et al (2006) 4.7% (parents' reports) or 5.0% (teachers' reports) of the children in the present sample had clinically significant externalizing problems. The BPI externalizing scale includes 11 items, all of which are represented in the CBCL and TRF externalizing scales.…”
Section: Ce (W2)-children Completed the Seven-item Coping Efficacy Scmentioning
confidence: 96%
“…The CBCL and TRF externalizing scales include two subscales: (a) rule-breaking behaviors (e.g., "Break rules at home, school or elsewhere") and (b) aggressive behaviors (e.g., "Cruelty, bullying, or meanness to others"). The CBCL and TRF scales are appropriate for ages 4 through 18 years and have satisfactory internal consistency (αs > .80) and test -retest reliability (rs > .80) in large-sample epidemiological studies with Chinese youth aged 6 -11 years (Leung et al, 2006;Liu et al, 1999Liu et al, , 2000. Leung et al (2006) found that CBCL/TRF externalizing scales predicted clinical diagnoses of oppositional defiant disorder/conduct disorder in Chinese children in Hong Kong.…”
Section: Ce (W2)-children Completed the Seven-item Coping Efficacy Scalementioning
confidence: 99%
See 2 more Smart Citations
“…On a 3-point scale of 0 (not true), 1 (somewhat or sometimes true), and 2 (very true or often true), adolescents indicated the extent to which they had committed specific behaviors in the past six months at the T1 and T2 assessments (␣ = 0.92 at both assessments). This measure was translated into Chinese and used widely in previous research (e.g., Leung et al, 2006). Parents responded to the Children Behavior Checklist (CBCL; Achenbach & Rescorla, 2001) to measure their children's problem behaviors (␣ = 0.92 at both assessments).…”
Section: Methodsmentioning
confidence: 99%